Effects of a partial ban on Papua New Guinea’s imports of poultry products - Gimiseve, Harry; Miamba, Nelson; Na'ata, Bartholomew; Dorosh, Paul A.; Schmidt, Emily; Yadav, Shweta (International Food Policy Research Institute, 2024)
In 2023, Papua New Guinea introduced a partial ban on poultry imports from Australia and Asian countries (representing about 70 percent of total PNG poultry imports) in response to the biosecurity threat posed by Avian Influenza (bird flu). Such a restriction on supply has the potential to lead to sharp price increases, steep reductions in household consumption and greater food insecurity.